The Multifaceted Roles of MicroRNA-181 in Stem Cell Differentiation and Cancer Stem Cell Plasticity - Chun Yang; Rui Wang; Pierre Hardy (Cells)
Stem cells are undifferentiated or partially differentiated cells with an extraordinary ability to self-renew and differentiate into various cell types during growth and development. The epithelial–mesenchymal transition (EMT), a critical developmental process, enhances stem cell-like properties in cells, and is associated with both normal stem cell function and the formation of cancer stem cells. Cell stemness and the EMT often coexist and are interconnected in various contexts. Cancer stem cells are a critical tumor cell population that drives tumorigenesis, cancer progression, drug resistance, and metastasis. Stem cell differentiation and the generation of cancer stem cells are regulated by numerous molecules, including microRNAs (miRNAs). These miRNAs, particularly through the modulation of EMT-associated factors, play major roles in controlling the stemness of cancer stem cells. This review presents an up-to-date summary of the regulatory roles of miR-181 in human stem cell differentiation and cancer cell stemness. We outline studies from the current literature and summarize the miR-181-controlled signaling pathways responsible for driving human stem cell differentiation or the emergence of cancer stem cells. Given its critical role in regulating cell stemness, miR-181 is a promising target for influencing human cell fate. Modulation of miR-181 expression has been found to be altered in cancer stem cells’ biological behaviors and to significantly improve cancer treatment outcomes. Additionally, we discuss challenges in miRNA-based therapies and targeted delivery with nanotechnology-based systems.